The Effect of Networked Learning Model and Self-Efficacy on the Performance of Informatics Education Students in an Online Learning Environment: Pengaruh Model Belajar Berjejaring dan Efikasi Diri Terhadap Kinerja Mahasiswa Pendidikan Informatika Dalam Lingkungan Belajar Online - Alfiriani, Adlia; Rini, Faiza; Darman, Regina Ade; Novita, Rini (Indonesian Journal of Innovation Studies, 2024)
Online learning is becoming very popular nowadays in higher education, this is due to the increasing use of digital technology and the internet, the need to increase student affordability. The learning network model has been developed as an effective learning design in online learning which can be the right solution for. However, currently no empirical evidence has been found regarding the role of the learning network model, especially as moderated by self-efficacy. The aim of this research is to determine the role of the learning network model and self-efficacy on the performance of informatics education students in an online learning environment. The research design used was semi-experimental with a 2x2 factor. A total of 109 informatics education students for learning evaluation subjects were then divided into two groups, namely experimental and control. The research results show that the learning network model and self-efficacy have a significant effect on student performance in the cognitive aspect, while there is no significant effect in the psychomotor aspect. Other factors This can occur because there are other factors that can support the achievement of student skills besides learning self-efficacy. Highlights: Significant Impact: The learning network model and self-efficacy significantly enhance cognitive performance in online learning environments. Limited Effect: No significant impact was found on psychomotor skills, indicating other factors influence skill development. Research Design: A semi-experimental 2x2 factor design was utilized with 109 informatics education students to assess the variables. Keywords: Learning Network, Online learning environment, Student performance, Self-efficacy, Informatics education